What app? Demographic and drug use predictors of buying drugs via different social media and messaging apps - van der Sanden R; Wilkins C; Parker K; Rychert M (Elsevier B V, 2026)
INTRODUCTION: Improving our understanding of how demographic and drug use factors shape social media drug market engagement is integral to targeting harm reduction and prevention responses to high-risk drug use and digital harm. AIM: To identify demographics and drug use patterns that correlate with using specific social media platforms to purchase drugs. METHODS: An anonymous online survey of New Zealanders who use drugs (N = 10,781) was used to explore social media drug purchasing. Logistic regression models were fitted to identify demographic and drug use correlates of using Facebook/Messenger, Snapchat, Instagram or high security apps (Telegram, Signal, Wickr) to purchase drugs. RESULTS: Sixteen percent reported purchasing drugs via social media (n = 1731). Facebook/Messenger was most used (54.2 %), followed by Snapchat (47.5), Instagram (24.7) and high security apps (17.6). Respondents aged under 30 were more likely to report using Snapchat and less likely to report using Facebook/Messenger or high security apps. Snapchat purchasers were more likely to be Asian, students, use MDMA/ecstasy and cocaine, and purchase via "friends/family". High security app purchasers were more likely to identify as male, reside in urban areas, use methamphetamine, psychedelics and cocaine, and purchase from a "drug dealer". Facebook/Messenger purchasers were more likely to report a low income, reside in small town/rural area; and purchase from "gang members", "drug dealers" and "friends/family". Instagram purchasers were more likely to report cocaine use and purchasing from "friends/family". CONCLUSIONS: Use of social media apps for drug buying are influenced by demographics (mainly age), drug market contexts, and drug type used.
Keywords: Hybrid drug markets; Social media-facilitated drug purchasing; Social supply; Youth drug use